Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Pendekatan Saintifik Mata Pelajaran Humas dan Keprotokolan Semester Gasal Kelas XI OTKP Di SMK YPM 3 Taman - Rini Indah Sari; Siti Sri Wulandari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
The purpose of this study is to analyze the feasibility of Student Activity Sheets (LKPD), describe the process of developing LKPD, and we can find out the responses of students in the Office Management Automation expertise program developed by LKPD. R&D with the 4D development model is the method used in research. And the limitations of this research are only at the development stage. A total of 20 students of class XI OTKP 3 SMK YPM 3 Taman became the subject of his research. The LKPD validation sheet includes the validation sheet for linguists, graphic experts, and material experts as well as students' response sheets obtained using research instruments. The stages of defining, designing, and developing are the research processes carried out at the stages that are in accordance with the 4D development model. Because the purpose of the research is only to develop and produce Student Activity Sheet (LKPD) products, the distribution phase is not carried out. The average results of the overall validation of experts on the feasibility of LKPD was 78.59% which included a component of language worthiness with a score of 72.86%, graphic worth 81.3%, and material eligibility 81.6%. By obtaining a score of 91.83% in the analysis of student responses with very good criteria, the developed LKPD can be used to support the learning process of PR and Protocol subjects very well as teaching material.